Characterization of Wheat Hull and Wheat Hull Ash as a Potential Source of SiO2 - Terzioglu, Pinar; Yucel, Sevil; Rababah, Taha M.; Ozcimen, Didem (NORTH CAROLINA STATE UNIV DEPT WOOD & PAPER SCI, 2013)
Wheat is a very important agricultural product, and is among the grains that has the highest sustenance value in the world. Every year large amounts of wheat hull is produced which has a low economic value. The present study aimed to characterize the structure of wheat hull and wheat hull ash obtained after burning wheat hull at 400 to 1000 degrees C for 5 h. This study also investigated the potential of wheat hull as a source for the production of silica xerogel. X-ray diffraction patterns, scanning electron microscope micrographs, the chemical properties, the particle morphology, particle size, surface chemistry of wheat hull, wheat hull ash, and its silica xerogels were determined by the use of various instruments and analysis techniques. A temperature of 700 degrees C was found to be the optimum ashing temperature with maximum amorphous silica content. The BET surface area of ashes ranged from 7.21 to 0.11 m(2)/g. The study demonstrated that silica xerogel powder with 93.9% silica content was obtained by the use of wheat hull after heat treating at 700 degrees C for 5 h.
Keywords: Adsorbent; Agricultural waste; Wheat hull; Wheat hull ash; Silica; Silica xerogel; RICE HUSK ASH; AQUEOUS-SOLUTION; MAGNESIUM-SILICATE; SURFACE-PROPERTIES; METAL-IONS; ADSORPTION; CADMIUM(II); PERFORMANCE; TECHNOLOGY; REMOVAL; Materials Science